Equilibrium Condition during Locomotion and Gait in Broiler Chickens - Alves,MCF (2016)
ABSTRACT The experiment was carried out with the objective of evaluating a methodology to estimate the angulation and equilibrium condition, relating them to gait score and the main diseases of the locomotion system in males and females of commercial broiler strains. A completely randomized experimental design in a factorial arrangement (2x2) was applied, consisting of two sexes and two genetic strains, with five replicates of 53 chickens each. The following characteristics related to broiler locomotion were studied: gait score (GS); incidence of Valgus (VAL) and Varus (VAR) deformities and of pododermatitis (POD); body angle relative the ground (ANG); equilibrium condition (EC); body weight (BW) and breast weight (BrW); and incidence of femoral degeneration (FD), tibial dyschondroplasia (TD) and spondylolisthesis (SPO). GS, and VAL and VAR were assessed inside a broiler house. Birds were then photographed to estimate ANG and EC. Birds were sacrificed at 42 days of age and analyzed for FD, TD, and SPO. Breast percentage was not influenced by sex or strain. Males showed better ANG than females, regardless of strain. Overall, the strains studied showed prostrated EC. The correlation between GS and the evaluated traits was low. There was a moderate to high association between EC and ANG both in males and females. GS showed low correlation with locomotion problems, and therefore, it is a poor indicator of skeletal diseases. On the other hand, the moderate to high correlations of ANG and EC with locomotion problems make them better indicators of bone diseases than gait score, which is possibly more related to EC and body posture than to bone pathologies.